2014
DOI: 10.5539/ass.v11n2p313
|View full text |Cite
|
Sign up to set email alerts
|

Linking Person-Job Fit, Person-Organization Fit, Employee Engagement and Turnover Intention: A Three-Step Conceptual Model

Abstract: Past studies revealed that the existence of congruence between employees and their job as well as organisation produces more favourable attitudes and behaviours. Although considerable research has been conducted on the person-job (P-J) fit and person-organization (P-O) fit, an in depth review of the literature identifies several research gaps. First, studies have largely focused on examining P-J fit and P-O fit separately. In addition, the relationship of P-J fit and P-O fit, and employee engagement has been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 43 publications
1
27
0
5
Order By: Relevance
“…Hollenbeck (1989); Manson and Carr (2011); Hamid and Yahya (2016); Sulistiowati et al (2018) found that person-job fit has a positive relationship with employee engagement. The finding also support the views of Memon et al (2015) that individuals who are fit with their job will feel confident with the work they do, more confidently with their roles in the job and tend to be engaged with their job. Also, based on the results of regression analysis, person-job fit has significantly explained 63.1% of variation in employee engagement in Edo state secretariat, Benin City.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Hollenbeck (1989); Manson and Carr (2011); Hamid and Yahya (2016); Sulistiowati et al (2018) found that person-job fit has a positive relationship with employee engagement. The finding also support the views of Memon et al (2015) that individuals who are fit with their job will feel confident with the work they do, more confidently with their roles in the job and tend to be engaged with their job. Also, based on the results of regression analysis, person-job fit has significantly explained 63.1% of variation in employee engagement in Edo state secretariat, Benin City.…”
Section: Discussionsupporting
confidence: 73%
“…Increased productivity, job satisfaction, job commitment, job engagement and reduced turnover intention becomes apparent as the congruence between an individual and a job increases [Iplik et al, 2011]. Individuals who are fit with their job will feel confident with the work they do, more confidently with their roles in the job and tend to be engaged with their job [Saks & Gruman, 2011;Memon et al, 2015]. In their study, Hamid and Yahya (2016) found that there is a strong and significant relationship between person-job fit and work engagement.…”
Section: Person-job Fit and Employee Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Certes, certains chercheurs ont tenté d'évaluer, dans une même recherche, les relations dyadiques entre la congruence P-O et P-J (p. ex., Chang, Chi et Chuang, 2010;Ali Memon et al, 2015), ces deux dernières dimensions étant certainement les plus étudiés selon Oh et al (2014). Par contre, aucune recherche ne semble avoir exploré à la fois les relations triadiques d'un modèle de congruence, c'est-à-dire entre l'employé, l'organisation et le superviseur (voir Personne-Organisation-Superviseur) et les relations triadiques d'un modèle de congruence entre l'employé, l'emploi et le superviseur (voir Personne-« Job »-Superviseur).…”
Section: Mireille Demers John Tivendellunclassified